Creating an algorithm for hard landing detection using aircraft flight data - Gunnarsson, Jacob; Angervall, Fredrik (My University, 2023)
Aircraft hard landings can cause damage to a landing gear or aircraft frame which in turn can cause a critical failure. As such, methods to detect hard landings have been created in different ways, for example, based on a pilot’s judgment or adding various sensors to a landing gear. The aim of the thesis is to identify existing hard landing detection methods and compare them in order to find a suitable concept to further evaluate in regards to application in a commercial aircraft. The literature review of current hard landing detection methods and interviews with aerospace engineers showed that using flight data parameters was a promising concept. A load predicting algorithm was created and tested in order to evaluate the concept. To make the algorithm, a CAD model of an arbitrary main landing gear (MLG) was first built for implementation in a multi-body dynamic model. This was then used to create a database of landing gear responses for different drop test simulations. Through sweeps over relevant parameters, longitudinal and normal tire forces were obtained for a spread of drop tests. The database was then used in the algorithm, based on an interpolation scheme, to give tire longitudinal and normal forces as an output at three critical instances. The outputs could in the future be used to decide whether a hard landing has occurred or not by comparing them to limits. It became evident that a good database is necessary for the algorithm to provide proper force estimations. The algorithm was accurate for an assumed runway friction. However, for a lower friction, the estimated forces were inaccurate. An alternative method using the angular velocity of the wheel to estimate the longitudinal force independent of friction was tested. While simplifications were made, it was shown that the method gave better estimations for low friction. Using aircraft flight parameters for detecting hard landings was proved to be a concept with potential. For implementation in commercial use however, several points were identified as requirements for it to be a reliable method with high fidelity and functionality.
Keywords: Structural Health Monitoring; Hard Landing Detection; Drop Test Simulation; Aircraft Landing Gear